Kinds of Participation to Short Leisure Time Activities of Athletes fromTurkish Weightlifting Championship - Meriç Eraslan; Mustafa Baş; Süleyman Can (Selcuk University, 2014)
This study is determining the kinds of participation to short leisure time activities of men and women athletes who have participated to the Turkish Inter-Clubs Weightlifting Championship and the ways in order to increase their success and performance. 66 women and 120 men, a total of 186 weightlifters from 40 different clubs which have participated to Turkish Inter-Clubs Weightlifting Championship held in theProvinceofMuğlaon November 2008 have participated to our research. The frequency, percentage distribution and the "t test" results have been displayed with tables and have been interpreted and estimated according to the above mentioned data. 0,05 is accepted as a statistical significant levels. As a consequence of this research, the Weightlifting Federation and the related clubs provide more material and immaterial opportunities to the men athletes as compared with women athletes for the leisure time's activities. On the other side, it has been observed that the athletes who mostly are graduated from high school maintain their own living by the intermediary of their father, that they do not receive information regularly from their federation and their own club in regard with  the appreciation of leisure times, that they do not read any publication in relation with the appreciation of leisure times, that they consider that the possibilities of the clubs are insufficient, that they do not participate to leisure time activities at a desired degree and that they state the economical insufficiency as a reason for this, however that in case they participate to leisure time activities they do not face any difficulty to spend time.